SISTEM PENGUASAAN LAHAN DAN PENDAPATAN PETANI PADA WANATANI KEMIRI DI KECAMATAN CAMBA KABUPATEN MAROS - Muh. Dassir (PERENNIAL, 2010)
Land tenure institution makkalice and mabbali on Timpuseng are not practice any more of the villagers. This causes many rabbing and decreases land holding (average 0.5 ha). While the farmers in Mariopulana village, still applying makkalice and mabbali, cause land holding still large enough (>1.5 ha). Land share cropper institution “teseng/ruma” and candle nut “mallolo” are still doing on family group, cause for helping. While in the institution of candle nut harvestig like makkampiri and makkalice, there are obtained pay system and there are not limited on the family group to get worker. The local knowledge of the land tenure in candle nut agroforestry can be basicly developed for tenure and land reform systems in social forestry. Through this system, they can maintain conservation and increase productivity of land without changing the forest status and functions. Those of landless farmers and land share priority for social forestry programs. Key words: Land tenure, farmer income, candle nut agroforestry